2007
DOI: 10.1007/s00382-007-0337-7
|View full text |Cite
|
Sign up to set email alerts
|

Observing upper troposphere–lower stratosphere climate with radio occultation data from the CHAMP satellite

Abstract: High quality observations of the atmosphere are particularly required for monitoring global climate change. Radio occultation (RO) data, using Global Navigation Satellite System (GNSS) signals, are well suited for this challenge. The special climate utility of RO data arises from their long-term stability due to their self-calibrated nature. The German research satellite CHAllenging Minisatellite Payload for geoscientific research (CHAMP) continuously records RO profiles since August 2001 providing the first o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 52 publications
2
141
0
Order By: Relevance
“…Previous studies have reported the oscillatory vertical structure over the Antarctica in the ECMWF temperature (e.g., Randel et al, 2004;Uppala et al, 2005;Manney et al, 2005). RO-derived temperature also captured similar features (e.g., Gobiet et al, 2005;Foelsche et al, 2008). Although both the phase measurement and the derived RO temperature are able to detect the oscillations, the important distinction between them is that the phase path offers a higher level of transparency when the focus is on identifying NWP errors.…”
Section: Resultsmentioning
confidence: 70%
“…Previous studies have reported the oscillatory vertical structure over the Antarctica in the ECMWF temperature (e.g., Randel et al, 2004;Uppala et al, 2005;Manney et al, 2005). RO-derived temperature also captured similar features (e.g., Gobiet et al, 2005;Foelsche et al, 2008). Although both the phase measurement and the derived RO temperature are able to detect the oscillations, the important distinction between them is that the phase path offers a higher level of transparency when the focus is on identifying NWP errors.…”
Section: Resultsmentioning
confidence: 70%
“…Our experience of building atmospheric climatologies utilizing RO data (e.g., Foelsche et al, 2008;Scherllin-Pirscher et al, 2011a) showed that 10 • zonal bands were a reasonable choice for calculating mean atmospheric profiles from RO data. These bands range from 90 • S to 90 • N, resulting in 18 zonal bands.…”
Section: Average Over High-quality Profilesmentioning
confidence: 99%
“…Finally, errors in BAROCLIM are caused by discrete sampling times and locations of RO measurements (sampling error; see, e.g., Foelsche et al, 2008;Scherllin-Pirscher et al, 2011a). The sampling error depends on the number of profiles and atmospheric variability and can be estimated from reference data that reflect true spatial and temporal variability.…”
Section: Error Sourcesmentioning
confidence: 99%
“…Due to their high accuracy, RO data have significantly reduced systematic errors in global weather analyses (e.g., Healy and Thépaut, 2006;Cardinali, 2009) and their potential for 5 climate monitoring has been demonstrated with simulations studies (e.g., Leroy et al, 2006;Ringer and Healy, 2008;Foelsche et al, 2008b) and analyses (e.g., Foelsche et al, 2008aFoelsche et al, , 2009Ho et al, 2012;Steiner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%